Psychological perception of great powers’ performance in the Globe. The origins of Russophobia. Interview with Andrey Pavlovich Tsygankov, Professor, Chair of International Relations and Political Science, San Francisco State University, PhD (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2018)
The interview includes following topics: the state and prospects of bilateral relations between the US and Russia, analysis of the factor of the Russophobia phenomenon’s influence on the perception of Russia’s image and its foreign policy in the US in the academic environment and circles of the political establishment. Scientist admitted that today there are no conditions for allied relations between Russia and the United States. In the near future, attempts to normalize bilateral relations on the part of Russia will not lead to counteractions. Political elites are not ready to build bilateral relations in the format of alliance. The society is either trapped in prejudices, or awaiting the appearance of leaders that capable to build qualitatively new relations between Moscow and Washington. Describing the presence of Russia in the global media space, A.P. Tsygankov emphasizes the need to actively promote the positive image of Russia, taking into account geopolitical realities.